2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0434.r1
|View full text |Cite
|
Sign up to set email alerts
|

Medial ball and socket total knee arthroplasty

Abstract: Aims Between 15% and 20% of patients remain dissatisfied following total knee arthroplasty (TKA). The SAIPH knee system (MatOrtho, Surrey, United Kingdom) is a medial ball and socket TKA that has been designed to replicate native knee kinematics in order to maximize the range of movement, stability, and function. This system is being progressively introduced in a stepwise fashion, with this study reporting the mid-term clinical and radiological outcomes. Patients and Methods A retrospective review was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Diduch et al reported: late infection (two out of 103 knee joints, or 2%); polyethylene thinning and instability requiring change of the tibial component (one case each, or 1% each); and tibial component dislocation (three cases, or 3%) [24]. Katchky found seven major complications (7%) in patients with SAIPH TKA: one infection, two deep vein thromboses, one cerebrovascular event, and two patients with stiffness requiring manipulation under anaesthesia [31]. Wilson noted a significantly higher number of venous thromboembolic events and major cardiac events after TKA following unicom- Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diduch et al reported: late infection (two out of 103 knee joints, or 2%); polyethylene thinning and instability requiring change of the tibial component (one case each, or 1% each); and tibial component dislocation (three cases, or 3%) [24]. Katchky found seven major complications (7%) in patients with SAIPH TKA: one infection, two deep vein thromboses, one cerebrovascular event, and two patients with stiffness requiring manipulation under anaesthesia [31]. Wilson noted a significantly higher number of venous thromboembolic events and major cardiac events after TKA following unicom- Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, excellent and good outcomes account for 90-98% of cases in the follow-up period of three to 14 years [24][25][26][27][28][29][30][31], depending on the type of prosthesis and on the surgical technique. Thus, the results of this retrospective research are similar to those published by other authors, indicating the effectiveness of modified measured resection in cemented total knee arthroplasty performed with the PFC Total Knee System (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CR knees used by surgeons in this study are proven to demonstrate low cumulative percent revision on the Australian Orthopaedic Association National Joint Replacement Registry. The MS TKA examined in this study uses a "ball-and-socket" design philosophy with a spherical medial femoral condyle (the "ball") articulating with a highly congruent spherical polyethylene bearing surface (the "socket") with 5-year results recently reported [3]. This arrangement facilitates near-perfect conformity across the bearing surface that maximizes the contact surface area (spherical-contact) and eliminates both point loading and sliding motion because of shear forces across the bearing surface (Fig.…”
Section: Methodsmentioning
confidence: 99%